Heterogeneous neurodevelopmental disorders in children with Kawasaki disease: what is new today? - Chien-Heng Lin; Wei-De Lin; I-Ching Chou; Inn-Chi Lee; Syuan-Yu Hong (BMC Pediatrics, 2019)
Abstract Background Kawasaki disease (KD) is a common vasculitis of childhood in East Asia. The complications of KD ascribed to long-term cardiovascular sequelae are considerably diverse. Although studies have investigated neurodevelopmental problems following KD in the past few decades, they have reported inconsistent conclusions. This study investigated potential epilepsy and associated neurodevelopmental disorders (NDDs) following KD in Taiwanese children. Methods We retrospectively analyzed the data of children aged < 18 years with clinically diagnosed KD from January 1, 2005, to December 31, 2015. These patients were followed up to estimate the prevalence of epilepsy and associated NDDs in comparison with the prevalence in general pediatric population in Taiwan and worldwide. Results A total of 612 patients with an average age of 1.6 years were included. The prevalence of associated NDDs was 16.8% (n = 103/612) in the study group, which consisted of epilepsy, intellectual disability (ID), autism spectrum disorders, Tourette syndrome (TS), attention deficit hyperactivity disorder, (ADHD), and others. Moreover, children with KD had a higher prevalence of epilepsy and TS in both Taiwan and worldwide (epilepsy: 2.61% in the KD group vs 0.33% in Taiwan and 0.05–0.8% in worldwide, p < 0.05; TS: 2.77% in the KD group vs 0.56% in Taiwan and 0.3–1% in worldwide, p < 0.05). The prevalence of ID, ADHD, and developmental language disorders was not significantly different between our study patients and those in Taiwan or worldwide. Conclusions Results revealed a higher prevalence rate of NDDs, especially epilepsy and TS, in Taiwanese children with KD than in the general pediatric population in Taiwan. However, these NDDs could be heterogeneous. Children diagnosed with KD were followed up because they had a higher risk of heterogeneous NDDs.